2018
DOI: 10.1373/jalm.2017.024679
|View full text |Cite
|
Sign up to set email alerts
|

Thrombophilia: Women-Specific Reference Ranges Can Prevent Misdiagnosis in Women

Abstract: Background: Thrombophilia is a state where abnormalities of the hemostatic system predispose a patient to thrombosis. Some coagulation factors are generally lower in women than in men. Therefore, the use of routine reference ranges (RRRs) based on male or mixed-sex groups may be misleading in the diagnosis of thrombophilia in women. We hypothesize that this affects the analysis of thrombophilia after pregnancy complications. Therefore, the aim of our study was to investigate the effect of women-specific refere… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 25 publications
(45 reference statements)
0
1
0
Order By: Relevance
“…Some studies have confirmed that there are differences between male and female in coagulation indicators, including AT, PC, fPS, FVII and FVIII [21][22][23] . The study of Veen et al confirmed that the use of routine RIs had a higher misdiagnosis rate than that of women-specific RIs 24 . Racial differences also affect coagulation indicators.…”
Section: Discussionmentioning
confidence: 93%
“…Some studies have confirmed that there are differences between male and female in coagulation indicators, including AT, PC, fPS, FVII and FVIII [21][22][23] . The study of Veen et al confirmed that the use of routine RIs had a higher misdiagnosis rate than that of women-specific RIs 24 . Racial differences also affect coagulation indicators.…”
Section: Discussionmentioning
confidence: 93%